Identification of disulfidptosis- and ferroptosis-related transcripts in periodontitis by bioinformatics analysis and experimental validation - Fu, Yu; Xu, Tingrui; Guo, Mengru; Lv, Wenhao; Ma, Ning; Zhang, Li (Frontiers in Genetics, 2024)
1) Background: Disulfidptosis and ferroptosis are forms of programmed cell death that may be associated with the pathogenesis of periodontitis. Our study developed periodontitis-associated biomarkers combining disulfidptosis and ferroptosis, which provides a new perspective on the pathogenesis of periodontitis.(2) Methods: Firstly, we obtained the periodontitis dataset from public databases and found disulfidptosis-and ferroptosis-related differentially expressed transcripts based on the disulfidptosis and ferroptosis transcript sets. After that, transcripts that are tissue biomarkers for periodontitis were found using 3 machine learning methods. We also generated transcript subclusters from two periodontitis microarray datasets: GSE16134 and GSE23586. Furthermore, 3 transcripts with the best classification efficiency were further screened. Their expression and classification efficacy were validated using qRT-PCR. Finally, periodontal clinical indicators of 32 clinical patients were collected, and the correlation between 3 transcripts above and periodontal clinical indicators was analyzed.(3) Results: We identified 6 transcripts that are tissue biomarkers for periodontitis, the top three transcripts with the best classification, and delineated 2 expression patterns in periodontitis.(4) Conclusions: Our study found that disulfidptosis and ferroptosis were associated with immune responses and may involve periodontitis genesis.